1984
DOI: 10.1111/j.1600-0447.1984.tb01221.x
|View full text |Cite
|
Sign up to set email alerts
|

Plasma pattern of adrenocorticotropin and cortisol during electroconvulsive therapy in patients with major depressive illness

Abstract: Thirty-three patients with major depressive illness were treated with electroconvulsive therapy (ECT) and plasma adrenocorticotropin (ACTH), and cortisol levels were measured 30 min before and 1, 5, 15, 30 and 60 min after ECT. There was an immediate release of ACTH with a maximum after 5 min. The maximum cortisol plasma levels were measured 30 min after ECT. No change in ACTH and cortisol concentrations was seen in control experiments when the patients received only anaesthesia. ACTH release was seen in patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
9
0

Year Published

1985
1985
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 22 publications
6
9
0
Order By: Relevance
“…Baseline cortisol levels were 30% greater in patients than in controls, but there were no differences from baseline levels after ECT sessions are consistent with the findings reported by Aperia et al, 16 Aperia et al, 20 Weizman et al 23 and Ozsoy et al 40 Ozsoy et al 40 suggested that the mechanism of action of ECT might be explained by the fact that it changes the instability of levels of neuroactive steroids that affect gamma-aminobutyric acid (GABA)…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Baseline cortisol levels were 30% greater in patients than in controls, but there were no differences from baseline levels after ECT sessions are consistent with the findings reported by Aperia et al, 16 Aperia et al, 20 Weizman et al 23 and Ozsoy et al 40 Ozsoy et al 40 suggested that the mechanism of action of ECT might be explained by the fact that it changes the instability of levels of neuroactive steroids that affect gamma-aminobutyric acid (GABA)…”
Section: Discussionsupporting
confidence: 79%
“…7 Glucocorticoids interact with their receptors in multiple target tissues, including the HPA axis, and are 15 Acute ECT has been consistently associated with improvement in plasma levels of cortisol. [16][17][18][19] Studies have found that the levels of cortisol and ACTH measured Individuals in the control group, recruited among hospital employees, were matched for sex and age.…”
Section: Introductionmentioning
confidence: 99%
“…Yet, the meaning of this observation is unclear since cortisol peak levels were not significantly different between the first and sixth ECT. In another study (Aperia et al 1984) the decrease in cortisol response to the sixth ECT in comparison to the first ECT was accompanied by a parallel decrease in ACTH release. The amplification in responsiveness offl-EP secretion immediately after repeated ECT stimulation is in accordance with the well-known clinical phenomenon that a single ECT is not sufficient, and a course of ECTs is required for successful treatment of depression.…”
Section: Discussionmentioning
confidence: 94%
“…As a part of a larger psychoendocrinological study of ECT in patients with major depressive illness, we measured the blood levels of ACTH, cortisol, prolactin (PRL), thyrotropin (TSH) , growth hormone (GH), somatomedins, melatonin and prostaglandin in connection with ECT. There was a rapid increase of ACTH and cortisol (3). The amplitude of hormonal release was lower at the end of an ECT series when the patients were regularly in remission.…”
mentioning
confidence: 90%